THE EFFECT OF TEACHING TECHNIQUE AND STUDENTS’ MOTIVATION ON STUDENTS’ NARRATIVE WRITING ACHIEVEMENT - Kesumaningrum, Eka (Majalah Ilmiah Kaputama, 2018)
The objectives of this study are to find out whether 1) The Differences of The Students Achievement which were taught by Story Circle Technique and Think Pair Share Technique ,(2) The Differences between the Learning Achievement of the Students who have Intrinsic Motivation and Extrinsic Motivation in Learning Writing Narrative,(3) Interaction Between Teaching Strategy and Learning Motivation in Learning Writing Narrative. An experimental research with factorial design 2x2 was used in this study. There were 80 students of grade XI of 202/2013 academic year of SMA Muhammadiyah 18 Sunggal  as Sample of this study. The students were divided into two groups, an experimental group an a control group. The random sampling techniques was applied to take the sample. The first group as an experimental group consists of 40 students with intrinsic motivation was given treatment by Think Pair Share and the second groups as a control group that also consist of 40 students with extrinsic motivation was given treatment by using Story Circle. The findings shows that (1) the average of students score which were taught by Story Circle is 75.75 and Think Pair Share is 71.47 with F observed= 2.571> F table= 2.321 (2) the average of students score who have intrinsic motivation is 75.7 and extrinsic motivation is 71.5 with F observed= 0.0001< F table= 2.323 Ho accepted Ha rejected.(3) there is interaction between teaching technique and students motivation on students narrative writing achievement with F observed= 17.423> F table= 2.285. Thus, it can be concluded that (1) The students achievement in writing narrative of which were taught by using Story Circle Technique is significantly higher than of the students taught by using Story Planner Strategy,(2) The Student achievement in writing narrative who have extrinsic motivation is significantly higher than that of the students who have intrinsic motivation (3) there is significant interaction between story circle technique and think pair share technique and students’ motivation to the students’ achievement in writing narrative. It implied that teachers should apply teaching strategies which are suitable with studets’ motivation so that the students can improve students’ achievement in writing narrative.